Sequential karyotyping in Burkitt lymphoma reveals a linear clonal evolution with increase in karyotype complexity and a high frequency of recurrent secondary aberrations. (24th June 2015) - Aukema, Sietse M.; Theil, Laura; Rohde, Marius; Bauer, Benedikt; Bradtke, Jutta; Burkhardt, Birgit; Bonn, Bettina R.; Claviez, Alexander; Gattenlöhner, Stefan; Makarova, Olga; Nagel, Inga; Oschlies, Ilske; et al.
Summary Typical Burkitt lymphoma is characterized by an IG‐MYC translocation and overall low genomic complexity. Clinically, Burkitt lymphoma has a favourable prognosis with very few relapses. However, the few patients experiencing disease progression and/or relapse have a dismal outcome. Here we report cytogenetic findings of seven cases of Burkitt lymphoma in which sequential karyotyping was performed at time of diagnosis and/or disease progression/relapse(s). After case selection, karyotype re‐review and additional molecular analyses were performed in six paediatric cases, treated in Berlin‐Frankfurt‐Münster‐Non‐Hodgkin lymphoma study group trials, and one additional adult patient. Moreover, we analysed 18 cases of Burkitt lymphoma from the Mitelman database in which sequential karyotyping was performed. Our findings show secondary karyotypes to have a significant increase in load of cytogenetic aberrations with a mean number of 2, 5 and 8 aberrations for primary, secondary and third investigations. Importantly, this increase in karyotype complexity seemed to result from recurrent secondary chromosomal changes involving mainly trisomy 21, gains of 1q and 7q, losses of 6q, 11q, 13q, and 17p. In addition, our findings indicate a linear clonal evolution to be the predominant manner of cytogenetic evolution. Our data may provide a biological framework for the dismal outcome of progressive and relapsing Burkitt lymphoma.